The impact of artificial intelligence on labor relations - Nurmagambetov А.М.; Zhumabaeva А.Б. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2022)
The article discusses the impact of technocratic evolution on the development and future of labor relations. The purpose of the study was to identify the features and characteristic features of the dissemination of the results of artificial intelligence in the field of labor. Digital economy and digitalization have modified the usual understanding of legal relations in the field of labor, giving labor relations an intangible character, close to civil law. The increasing role of artificial intelligence in production entails a number of problems that Kazakhstan is going to face. One of the most pressing and common problems includes issues of unemployment, the protection of personal data.